Experimental Justification of Effectiveness of Cord Blood Serum-Derived Biological Product for Correction of Autoimmune Thyroiditis - Kurylko, Yuliia (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):300